Outbreak of Infection with Extended-Spectrum β-Lactamase-Producing Klebsiella pneumoniae in a Mexican Hospital - Silva, Jesus (American Society for Microbiology, 2001)
Thirty-one strains of Klebsiella pneumoniae (including 10 duplicates) from 21 septicemic pediatric patients (age, <2 months) were studied during a 4-month period (June to October 1996) in which the fatality rate was 62% (13 of 21). These isolates identified by the API 20E system yielded the same biotype. Pulsed-field gel electrophoresis experiments revealed the same clone in 31 strains. The isolates were multidrug-resistant but were still susceptible to ciprofloxacin, imipenem, and cefoxitin. A 135-kb plasmid was harbored in all of the isolates. No transconjugants were obtained that were resistant to ampicillin, cefotaxime, tetracycline, or gentamicin. Isoelectric focusing for β-lactamases was performed on all strains, and three bands with pIs of 5.4, 7.6, and 8.2 were obtained. Of these, the pI 8.2 β-lactamase had an extended-spectrum β-lactamase phenotype. PCR amplification of both TEM- and SHV-type genes was obtained. The sequence analysis of the SHV PCR product indicated a mutation corresponding to the SHV-5 β-lactamase.